How T-cruiscape shapes the flow experience of passenger's well-being - Gonzáles-Santiago, M. S.; Loureiro, S. M. C.; Langaro, D. (International Journal of Hospitality Management, 2025)
Understanding the new T-cruiscape (a servicescape integrated with technological services in the cruise industry) onboard cruise ships is key for managers. Therefore, this research integrated the T-cruiscape, flow experience, and subjective well-being within the Stimuli–Organism–Response framework to examine how the T-cruiscape shapes the passenger flow experience and enhances their well-being and how discomfort acts as a moderator in this relationship. A mixed-method approach was adopted, including 35 interviews with crew members who were experienced in working with these technologies and passengers, followed by a survey of 358 passengers who had used these technologies. Qualitative data analysis was conducted using MaxQda2020, while quantitative data was analyzed using SmartPLS4. The findings from interviews corroborated the seven facets of T-cruiscape, which were then considered in the main study. T-cruiscape acting as stimuli can generate flow experience and, subsequently, passengers' subjective well-being through desirable feelings. The discomfort passengers feel when using technology can strengthen the relationship between the T-cruiscape and the flow experience. The theoretical and practical implications of the research provide valuable insights into potential marketing practices and suggest avenues for future research.